Acceptability Of The “Dasunse” Website-Based Learning Media with The Merdeka Learning Pathway in Elementary Schools Across West Java - Riyadi Rafiki; Yusuf Tri Herlambang; Budi Hendrawan; Ai Sutini; Yoga Prima Putra; Rahman Wahid (CV. Ksatria Siliwangi, 2025)
The use of technology in the learning process in schools today is often used to support teachers in teaching. The use of technology in education by teachers in elementary schools can enrich students' learning experiences, so it is important for teachers to utilize technology as a tool in learning. Web-based learning media is a form of using technology in education, which is implemented in the teaching and learning process using technology. Research regarding the use of website-based learning media has been well received, and researchers will examine the acceptance of Website-Based Learning Media with the Independent Learning Model by teachers throughout West Java. This research was conducted using a quantitative research approach. The research method that researchers used was a correlational survey with path analysis. The results of the research show that the creation of website-based digital media with an independent flow in the West Java region is well received, this can be seen from the results of Self-Efficacy (Self Application) which has a relationship with Behavioral Intention (Technology Acceptance) which has good acceptance seen from the value above that The response results related to these indicators are influenced by self-influence and efforts to use media which are the main determinants in the acceptance and effectiveness of learning media.